History of Islam- Uthman Ibn Affan - (R.A) - Maulvi Abdul Aziz (RIYADH Darussalam publisher, 2012)
Our past, present, and future are interconnected and interdependent. Therefore, knowing and understanding our history is not optional: it is essential. Darussalam presents the entire History of Islam to our youth in language that appeals to them. in a simple yet lucid manner. The first four volumes in this series explore Islamic history during the period of the first Four Rightly Guided Caliphs Later volumes would be devoted to the History of Islam, down through the ages to modern times, in sha Allah.